LEADING IN THE TIME THAT REMAINS: The Passion and Complexity of Paul’s Leadership in 1 Corinthians - Duckor, Brent; Racine, Jean-François (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2022)
Paul of Tarsus sought to lead Gentiles toward Israel with a passion, style, and commitment that invite us to study his leadership model with a concrete congregation, the Corinthians. After discussing what is known about Paul and the Corinthian congregation, the article explains further his project for this group and how its adoption of Paul’s message puts them in a delicate and difficult position. The article then presents three case studies (1 Cor 1:10-12; 5:1-4; 12) that examine how Paul exercises leadership relevant for today’s leadership studies. Using a standard modern work, The Leadership Challenge, the article shows how Paul’s exercise of leadership in 1 Corinthians converges with some best practices of leadership described by Kouzes and Posner, but also collides with these prescriptions. The article concludes that Paul appears as an audacious and refreshingly authentic leader dedicated to his commission to bring this group in proximity to Israel. From this study emerges the portrayal of a complex, principled leader who must lead at multiple levels within and across a community.